Linguocultural Specifics of Artificial Intelligence Representation in the English Language Media Discourse: Corpus-Based Approach - Larisa A. Kochetova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2023)
The article deals with the discursive construction of artificial intelligence (AI) in the English-language media discourse. Corpus methods establish semantic, figurative-perceptual and axiological specificity in the media representation of AI in various media segments, such as tabloids and broadsheet papers. Corpus-assisted discourse analysis includes: 1) identification of unique semantic domains that determine discourse interpretations of this socially significant phenomenon, followed by an analysis of their dispersion in narratives about AI; 2) analysis of the figurative-evaluative and value content of its media representation; 3) investigation of the specifics of broadsheet media and tabloid media representations of the AI concept. It was found that AI receives multiple media representations, in which its conceptual features represented by the lexical items of the semantic fields “Knowledge”, “Ability”, “Information and Computer Technologies” are supplemented and enriched by the lexical units of the semantic fields “Safety/Danger”, “Transformation”, “Ethics”. In media narratives about AI, the concept of “imitation of human abilities” is often associated with fake news, plagiarism, warfare, crime, climate change, and unemployment. Corpus data revealed that in the narratives about AI in broadsheet media, the lexical items of the semantic field “Robots” emphasize the similarity of AI with anthropomorphic entities; the semantic field “Competition” represents the idea of a rivalry between a human and a machine, as well as between countries, governments and companies; the semantic field “Warfare” actualizes the pragmatics of warning related to collective security and expressing public concern about the possible negative consequences of the development of AI. Popular media emphasize the androgenic nature of AI, its entertainment potential (“Games”), practical values related to health care (“Medicines and Treatment”); and the pragmatics of warning related to individual safety (“Crime”). The evaluative media representation of AI is formed mainly by ethical and practical, often negative, evaluative features transmitted through metaphoric images, intertextual references, and cultural models that determine the behavioural patterns of the discursive community members.